Building the Infrastructure for Sustainable Digital Mental Health: It Is “Prime Time” for Implementation Science - Gillian Strudwick; Iman Kassam; John Torous; Sean Patenaude (JMIR Mental Health, 2025)
AbstractDespite the growing enthusiasm for and a proliferation of digital mental health innovations, their integration into routine clinical care remains limited—often stalled at the pilot, research, or demonstration stage. This editorial argues that the successful adoption, scale-up, and sustainability of digital mental health innovations require intentional infrastructure, not just technology. Using the Non-Adoption, Abandonment, Scale-Up, Spread, and Sustainability (NASSS) implementation science framework, we examine how challenges across the seven framework domains (condition, technology, value proposition, adopters, organization, wider context, and their interactions over time) continue to hinder meaningful progress. We describe a focused digital mental health innovation infrastructure as a model for overcoming these barriers. Drawing on experiences from the Digital Innovation Hub at Canada’s largest mental health and addictions teaching hospital, we illustrate how investing in the right infrastructure may move digital mental health innovations from “promising” to “impactful.” We call for global collaboration to share knowledge and accelerate the real-world integration of digital innovations in routine mental health clinical care.